1976
DOI: 10.2466/pr0.1976.38.1.267
|View full text |Cite
|
Sign up to set email alerts
|

Are “Fat-Girls” More Hypnotically Susceptible?

Abstract: 258 girls who volunteered for a weight control program were administered the Harvard Group Scale of Hypnotic Susceptibility. Their scores were significantly higher than other groups reported in the literature. It is speculated that either a basic personality trait or the demand characteristics of the weight program contributed to the group's unusually high hypnotic susceptibility performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Thorne, Rasmus, and Fisher (1976) were the first to report an obese group of patients as having a higher mean score (9.17) on the HGSHS:A. Alternatively, Deyoub (1978) (Barber & Glass, 1962) and found no significant relationship between obesity and suggestibility, as measured by the Barber scale. Andersen (1985), using the SHSS:C, arguably a more accurate measure of hypnotizability, found that the percentage overweight was significantly related to hypnotizability test scores, r = .56, p < .001.…”
Section: Links With Self-defeating Overeatingmentioning
confidence: 87%
“…Thorne, Rasmus, and Fisher (1976) were the first to report an obese group of patients as having a higher mean score (9.17) on the HGSHS:A. Alternatively, Deyoub (1978) (Barber & Glass, 1962) and found no significant relationship between obesity and suggestibility, as measured by the Barber scale. Andersen (1985), using the SHSS:C, arguably a more accurate measure of hypnotizability, found that the percentage overweight was significantly related to hypnotizability test scores, r = .56, p < .001.…”
Section: Links With Self-defeating Overeatingmentioning
confidence: 87%
“…Concern with weight and eating behavior may be correlated with hypnotic susceptibility in women (Groth-Marnat 6r Schumaker, 1990). It is also possible that overweight women are more hypnotically susceptible (Thorne, Rasmus, & Fisher, 1976; but see also Deyoub, 1978).…”
Section: Concl Us R Onmentioning
confidence: 99%